Effects of Experimental Tooth Clenching on Pain and Intramuscular Release of 5-HT and Glutamate in Patients With Myofascial TMD. Issue 8 (August 2015) - Dawson, Andreas; Ghafouri, Bijar; Gerdle, Björn; List, Thomas; Svensson, Peter; Ernberg, Malin
<x xml:space="preserve">Abstract</x> Objectives: It has been suggested that tooth clenching may be associated with local metabolic changes, and is a risk factor for myofascial temporomandibular disorders (M-TMD). This study investigated the effects of experimental tooth clenching on the levels of 5-HT, glutamate, pyruvate, and lactate, as well as on blood flow and pain intensity, in the masseter muscles of M-TMD patients. Methods: Fifteen patients with M-TMD and 15 pain-free controls participated. Intramuscular microdialysis was performed to collect 5-HT, glutamate, pyruvate, and lactate and to assess blood flow. Two hours after the insertion of a microdialysis catheter, participants performed a 20-minute repetitive tooth clenching task (50% of maximal voluntary contraction). Pain intensity was measured throughout. Results: A significant effect of group (P<0.01), but not of time, was observed on 5-HT levels and blood flow. No significant effects of time or group occurred on glutamate, pyruvate, or lactate levels. Time and group had significant main effects on pain intensity (P<0.05 and <0.001). No significant correlations were identified between: (1) 5-HT, glutamate, and pain intensity; or between (2) pyruvate, lactate, and blood flow. Discussion: This experimental tooth clenching model increased jaw muscle pain levels in M-TMD patients and evoked low levels of jaw muscle pain in controls. M-TMD patients had significantly higher levels of 5-HT than controls and significantly lower blood flow. These 2 factors may facilitate the release of other algesic substances that may cause pain.